Use and Production of FLOSS in Brazilian Government: an Wide Survey - Lisboa, Flávio Gomes da Silva; Beatriz, Marilene Zazula (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2021: Anais do XVIII Congresso Latino-Americano de Software Livre e Tecnologias Abertas, 2021)
This article presents a quantitative and qualitative exploratory research on the use and production of free/libre and open source software (FLOSS) by Brazilian federal government institutions. 167 federal institutions were interrogated through the Brazilian government's Integrated Ombudsman and Access to Information Platform, Fala.BR, and other specific eletronic information request forms between 2018 and 2020. This is the most extensive survey on the results of 13 years of federal policies to encourage the use of free software in Brazil. This research shows which are the most used software and software categories, the licenses that occur the most, the biggest FLOSS users in the government and which free and open source software were produced and by which institutions.